2017
DOI: 10.1002/jmri.25867
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of the placental anatomy and perfusion in a mouse model of intrauterine inflammation

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1260-1267.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…We speculate that these effects may contribute to the formation of a clot, subsequently decreasing placental volume. The results of our current study add further support to this speculation and correlate the acute placental injury following IUI to fetal sequelae [45].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We speculate that these effects may contribute to the formation of a clot, subsequently decreasing placental volume. The results of our current study add further support to this speculation and correlate the acute placental injury following IUI to fetal sequelae [45].…”
Section: Discussionsupporting
confidence: 81%
“…Our study is supported by our prior work investigating MRI-based placental perfusion deficits following the exposure to IUI [44]. Specifically, we used MRI to examine placental damage following IUI and found a significant decrease in capillary blood volume and velocity, suggestive of vascular damage and blood flow disruption [44,45,46]. We speculate that these effects may contribute to the formation of a clot, subsequently decreasing placental volume.…”
Section: Discussionsupporting
confidence: 78%
“…LPS itself has been shown to induce hypoglycemia (Tweedell et al., 2011; Yanay, Bailey, Kernan, Zimmerman, & Osborne, 2015). Wu et al (2018) reported that after intrauterine injection of LPS, magnetic resonance imaging (MRI) showed significantly decreased placental perfusion, and the placental capability in response to maternal glucose challenge was impaired. These studies indicate that LPS‐induced IUI may affect the energy substrate intake of the fetal brain and lead to abnormal neuron cells growth and metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that, at this time point, the inhibited mTOR activity in LPS fetal brains is linked with insufficient energy supply from mother to fetus. Wu et al (2018) observed that at 6 hr after intrauterine injection of LPS, MRI showed significantly decreased placental perfusion, suggesting the LPS fetal brains may not be obtaining enough nutrients. Subsequently, after 24 hr of LPS exposure, mTOR signaling displays an overall inhibition in LPS fetal brains based on the low expression of p‐mTOR, p‐4Ebp1, p‐S6k, and p‐rpS6.…”
Section: Discussionmentioning
confidence: 99%
“…This model mimics the most common clinical scenario associated with preterm birth. In this model, we have previously identified acute maternal vascular malperfusion (MVM) with IVIM and immunohistochemistry measurements in the placenta [47], and thus, the model serves as an ideal test bed for potential clinical translation of DGE MRI to assess placental function. In this study, we performed DGE MRI to examine the time-resolved placental response to a glucose challenge in LPS- exposed placentae, in comparison with the controls.…”
Section: Introductionmentioning
confidence: 99%